ANALISIS KETERAMPILAN METAKOGNITIF PESERTA DIDIK DALAM PEMBELAJARAN BIOLOGI MELALUI ASESMEN PEMECAHAN MASALAH DI MAN 3 PALEMBANG - Patmawati Patmawati; Indah Wigati; Kurratul 'Aini (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
Metacognition is a level in the thinking process that students can use to adjust their minds to solve problems, one's awareness or knowledge of the processes and results of thinking as well as the ability to control and evaluate these processes. This study aims to analyze the metacognition skills of class X IPA students in biology learning through problem-solving assessments at MAN 3 Palembang. This research is a type of quantitative descriptive research using pre-experiment design and One Group Posttest Design. The sample was determined using purposive sampling of 34 students. Data collection was carried out using problem-solving assessments and then the MAI questionnaire was given to students after problem-solving activities. The research data were then analyzed based on the assessment criteria of problem solving questions and interpretation of inventory values from the metacognition skills questionnaire. The results of this study indicate that students have the ability to solve problems in the very high category on the indicator of making plans which shows that students in solving a problem have succeeded in using their metacognitive skills on indicators of conditional knowledge and planning abilities as evidenced by the success of students in answering questions. The conclusion of this study is that students are able to use metacognition skills through problem solving assessments.